غريب القرآن الكريم عند ابن جزي من خلال تفسيره الجزء الاول من القرآن الكريم أنموذجا - عروة, أميرة; بوسالم, مروة (University of eloued جامعة الوادي, 2022)
تم تسليط الضوء في هذا البحث على شخص الإمام ابن جزي رحمه الله وتفسيره, وبما أن الدراسة تتناول علم الغريب لجأنا إلى دراسة كنهه وما يتعلق به من أهمية وسبب وأدب وغيره, مع دراسة منهج ابن جزي رحمه الله في عرضه للغريب في كتابه, بالاطلاع على طريقته ومصادره وغيرها مما يستلزم لدراسة المنهج, كما تطرقنا بعد كل هذا إلى دراسة نماذج من الألفاظ الغريبة والتي كانت في خضم وثنايا الجزء الأول من القرآن, بعرض أقول ابن جزي فيها ودراستها مع بيان أقوال أهل العلم في من اللغة والغريب والتفسير.This research sheds light on the person of Imam Ibn Jazzi, may God rest his soul, and his explanation. Since the study deals with the science of the stranger, we resort to studying his essence and the related importance, reason, and literature, along with studying the curriculum of Ibn Jazzi, may God have mercy on him in his presentation of the stranger in his book, by looking at his methods, sources, and other things that are necessary to study the curriculum. We also went on to study models of strange words that were in the middle of the first part of the Koran, by displaying Ibn Jazzi in it and studying them with the sayings of scholars in language, stranger, and explanation.
علوم قرآن
Keywords: غريب القرآن، الإمام ابن جزي ،القرآن الكريم; Strange Qur'an, Imam Ibn Juzay, the Holy Qur'an, interpretion